PENGEMBANGAN MODEL PEMBELAJARAN SEJARAH BERBASIS KEUNIKAN TOPONIMI KAWASAN BANTEN LAMA UNTUK MENINGKATKAN HISTORICAL EMPATHY SISWA SMA NEGERI DI KOTA SERANG - Hadi Wibowo, Tubagus Umar Syarif; Sariyatun, S.; Djono, D. (Sebelas Maret University (UNS), 2018)
This study aims to: 1) find out the model of learning history which was held at SMA Negeri 4 Serang; 2) developed a model of learning-based history of the uniqueness of the area of Banten Lama toponimi which can boost the historical empathy of students; 3) knowing the effectiveness of model-based learning, the uniqueness of the area of Banten Lama toponimi to incrase historical empathy Senior High School 4 Serang.Research on the development model using a modified Borg and Gall which consists of 3 stages, namely: 1) preliminary studies, 2) model development, and 3) test the effectiveness of the model. The analysis of data used during the development of the descriptive analysis is the analysis of the feasibility of a model based on score criteria, and analysis tests the ability of the historical achievements of historical empathy and empathy learn history through the t-test.Results of the study it was concluded that: 1) model of learning history which was held at SMA Negeri 4 Serang hasn't been able to spur the growth of the social system, the reaction system, the impact of instructional; and support systems that can generate interest and historical empathy of students to understand and feel the situation of events and actions of the agents of history; 2) model-based learning uniqueness toponimi area Banten Lama has successfully developed with local history material characterisitics of holistic learning, cooperative learning, group-based syntax with the investigation and a contextual approach to improving historical empathy of students. Learning the history of the model developed is included in the category of